2010
DOI: 10.3174/ajnr.a2315
|View full text |Cite
|
Sign up to set email alerts
|

Functional MR Imaging Evidence of Altered Functional Activation in Metabolic Syndrome

Abstract: BACKGROUND AND PURPOSE:MetS is a cluster of risk factors associated with significant cardiovascular morbidity and mortality and diminished cognitive function. Given that little is known about the early signs of brain vulnerability related to persistent metabolic dysfunction, we set out to determine whether cognitively healthy middle-aged individuals with MetS exhibit an altered cerebrovascular response to a cognitive challenge relative to those without MetS. MATERIALS AND METHODS: Forty neurologically healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…Consistent with our results, a similar pattern of cortical change was described in a previous study of type 2 diabetes, which reported a loss of cortical gray matter in the insula and the left hemisphere (Moran et al 2013). In a functional imaging study, MS was associated with a significantly lower task-related BOLD response in the right superior frontal gyrus, right superior parietal lobule, and left inferior parietal lobule, despite intact global cognitive performance (Hoth et al 2011). In contrast, higher functional activation in the right superior parietal lobule was associated with better task performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our results, a similar pattern of cortical change was described in a previous study of type 2 diabetes, which reported a loss of cortical gray matter in the insula and the left hemisphere (Moran et al 2013). In a functional imaging study, MS was associated with a significantly lower task-related BOLD response in the right superior frontal gyrus, right superior parietal lobule, and left inferior parietal lobule, despite intact global cognitive performance (Hoth et al 2011). In contrast, higher functional activation in the right superior parietal lobule was associated with better task performance.…”
Section: Discussionsupporting
confidence: 90%
“…However, only a few studies on the regional distribution of brain atrophy in MS have been reported so far. These studies of small, selected samples have reported that MS is associated with early alterations in the structural and functional changes of the brain (Segura et al 2009;Hoth et al 2011). Although previous studies have demonstrated an association between MS and changes in cerebral white matter integrity (Segura et al 2009;Sala et al 2014), no study to date has evaluated either cortical thickness or subcortical volumes in MS using MRI.…”
Section: Introductionmentioning
confidence: 96%
“…The final study samples were diverse (less than 60% non-Hispanic Caucasian), well educated (average education level = 15 years), and cognitively intact (average Mini-Mental State Examination score, MMSE > 26 out of 30). We found that the intensity of working memory-related brain activation diminished with the development of metabolic and cardiovascular disorders as early as midlife, even when cognitive performance was still within normal limits [11,12,22,25,30]. These disorders included obesity, hypertension, metabolic syndrome, and frank cardiovascular diseases.…”
Section: Early Markers Of Brain Vulnerabilitymentioning
confidence: 98%
“…Lower brain activity in expected taskrelated brain regions [11,12,24,25], greater brain activity in expected task-related brain regions [15,17,19], significant recruitment of unexpected brain regions [43,44], and suspension of unrelated brain activity [22,23] have all been reported among normally performing at-risk individuals. Ubiquitous interpretations of diminished BOLD response to a cognitive challenge as both cognitive efficiency and impairment have limited our ability to extrapolate mechanisms through interpretations of isolated fMRI findings.…”
Section: Vascular and Nonvascular Mechanisms Of Cognitive Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation